Antiviral B cell memory in the absence of mature follicular dendritic cell networks and classical germinal centers in TNFR1-/- mice. - Karrer, U; López-Macías, C; Oxenius, A; Odermatt, B; Bachmann, M; Kalinke, U; Bluethmann, H; Hengartner, H; Zinkernagel, R (2000)
TNFR1-/- mice have been shown to lack networks of mature follicular dendritic cells (FDCs) and they do not form germinal centers. With nonreplicating Ags, IgG titers were inefficiently induced and not maintained. In this study, the neutralizing Ab response and the establishment of B cell memory in TNFR1-/- mice after infection with vesicular stomatitis virus (VSV) were analyzed histologically and functionally. Immunization with VSV-derived protein Ags without adjuvant induced only IgM but no IgG Abs in TNFR1-/- mice, whereas VSV glycoprotein emulsified in CFA or IFA induced IgM and IgG responses that were short-lived and of moderate titer. However, infection with live VSV induced excellent neutralizing IgM and IgG responses in TNFR1-/- mice, and adoptively transferable B cell memory was generated and persisted for more than 300 days. In contrast, IgG levels and Ab-forming cells in the bone marrow declined within 300 days by 90-95% compared with controls. These findings suggest that 1) increased Ag dose and time of Ag availability can substitute for FDC-stored Ab-complexed Ag in the induction of efficient IgG responses in TNFR1-/- mice devoid of classical germinal centers; 2) the induction and maintenance of adoptively transferable B cell memory can occur in the absence of Ag bound to mature FDCs; and 3) the long-term maintenance of elevated IgG titers is largely dependent on FDC-associated persisting Ag. However, about 5-10% of the Ab production remained in the absence of detectable persisting Ag in TNFR1-/- mice, probably either due to immature FDCs being partially functional and/or due to long-lived plasma cells.